Knowledge mapping and visualization of trends in immunotherapy for ovarian cancer over the past five years: a bibliometric analysis - Shaie, Kowthar Mohamed; Sihan, Lian; Yuli, Wang; Mengfei, Han; Renqian, Feng; Yan, Hu (Frontiers in Immunology, 2024)
Background: This study conducts a bibliometric literature analysis to explore trends in immunotherapy for ovarian cancer from 2019 to 2023. Methods: An extensive online literature search was conducted in the Web of Science Core Collection database to identify English-language articles and reviews related to "trends in immunotherapy", and "ovarian cancer". statistical analysis was performed using VOSviewer to visualize and compare nations, institutions, and journals simultaneously. Results: Our findings highlight contributions by 118 nations, led by the People's Republic of China with 3,167 contributions; Germany followed with 558 and Italy having 547. Of all publications made between 2019-2023, "Frontiers Immunology" had the most publications with 546 total records followed by "cancers ", and "frontiers in oncology" being the most heavily relied upon categories. Annually publication trends increased until 2022 but then declined considerably as a peak of highly-cited papers occurring between 2019 and 2022. Conclusions: Our bibliometric analysis not only maps the evolution of immunotherapy research in ovarian carcer but also provides actionable insights for advancing scientific progress. By identifying emerging trends and key areas, future research can strategically enhance treatment strategies and outcomes for ovarian cancer patients.